Managing the Poverty–CO2 Reductions Paradox: The Case of China and the EU. (December 2015) - Collins, Denis; Zheng, Chunfang
This article examines the "Poverty–CO2 (carbon dioxide) Reductions Paradox, " wherein reducing poverty through economic growth simultaneously increases CO2 emissions from increased production and consumption, at a time in history when CO2 emissions must be reduced to avoid climate change catastrophes. Paradox theory and integrative social contracts theory are applied to help understand the evolving behaviors of China, the world's largest CO2 emitter, and the European Union, a CO2 reduction leader, from 1990 to 2015 at the national and international levels. The environmental results of these activities have become species-threatening. The principle of fairness/justice is offered in order to guide efforts to resolve the paradox in a way that avoids irreversible climate changes projected to begin around 2050. Prominent stakeholder injustice claims are highlighted for future scholarship and policymaking considerations.